2018
DOI: 10.3329/ganit.v37i0.35721
|View full text |Cite
|
Sign up to set email alerts
|

Exact Traveling Wave Solutions to Benney- Luke Equation

Abstract: By using the improved (G/G) -expansion method, we obtained some travelling wave solutions of well-known nonlinear Sobolev type partial differential equations, namely, the Benney-Luke equation. We show that the improved (G/G) -expansion method is a useful, reliable, and concise method to solve these types of equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The BL equation appears in a variety study, such as exact solutions of BL equation were found by using enhanced   GG  -expansion method [26] analytic solutions of BL equation were obtained with the help of improved   GG  -expansion method [27], the exact solution was obtained using homogeneous balance method for BL equation [28], the shock wave solution of the BL equation was obtained using ansatz method [29], exact solutions of the BL equation were found by using modified simple equation method [24].…”
Section:   mentioning
confidence: 99%
“…The BL equation appears in a variety study, such as exact solutions of BL equation were found by using enhanced   GG  -expansion method [26] analytic solutions of BL equation were obtained with the help of improved   GG  -expansion method [27], the exact solution was obtained using homogeneous balance method for BL equation [28], the shock wave solution of the BL equation was obtained using ansatz method [29], exact solutions of the BL equation were found by using modified simple equation method [24].…”
Section:   mentioning
confidence: 99%
“…"So far as the exact solutions to NLEEs are concerned, the data furnished in the present study pertaining to their structure will assist in preventing the structure from claiming changes attributable to unpredictable physical phenomena." Among these endeavours are the strategy of homotopy examining, the strategy of sticking, the variable strategy of reiteration [8][9][10][11][12], the differential transforms method and Laplace transform [13][14][15] differential transforms method, Elzaki transform, double Laplace transform, the projected differential transform method [16][17][18][19][20][21][22] and Adomian decomposition (ADM) method [23].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we introduce an advanced method that relies on modified integral transform (MIT) [21], and one that uses simple techniques. Additionally, we contemplate the combination of MIT and the present technique to solve the B-L and SP-H equations [22].…”
Section: Introductionmentioning
confidence: 99%